플랜트 프로젝트 사업기획단계 표준 업무 프로세스 개발 - 사업발굴 및 사업참여 결정을 중심으로 - 이도윤; 최창훈; 원서경; 조문영; 한충희; 이준복; Lee, Do-yun; Choi, Chang-Hoon; Won, Seo-kyung; Cho, Moon-Young; Han, Choong-Hee; Lee, Junbok (한국건설관리학회 논문집, 17(4), 2016)
Recently, overseas plant orders of domestic enterprises are steadily increased, and the amount of orders in the first half of 2014 were 93% increased compared to the previous year. In addition, now which is the third quarter of 2015, overseas plant orders are already over 249.8 billion dollars so the interests of plant industry research has been increased. In the life cycle of the plant project, CM before the construction stage is to complement the uncertainties that are inherent in the early stages of the project, and from the viewpoint of supporting the rational decision-making, the importance of its role is on the rise. Among them, excavating and investing participation plan in the planning stage is an important work that has a large impact force to influence the success and failure of future project. However, the work has become a problem with frequent consultations due to decision-making, continuous modification, and inefficient repetitive tasks. Therefore, it is needed that work process should be changed to effectively accommodate. The purpose of this paper is to derive the major work items for excavating and investing participation plan in the planning stage of the plant project, and establish a standardized work process through the Delphi analysis. The result of this study is expected to be utilized for EPC companies in ensuring the technical competitiveness in planning on overseas markets, and improve the efficiency of work. 최근 국내 기업의 해외 플랜트 수주는 꾸준히 증가하는 추세이며, 2014년 상반기의 수주액은 전년도 대비 93% 이상 크게 증가되었다. 또한, 2015년 3사분기가 지난 현재, 해외 플랜트 수주액은 이미 2,498억 달러를 넘어섰다고 조사된 만큼 플랜트 산업에 대한 관심이 증가되고 있다. 플랜트 프로젝트의 생애주기 중 시공 이전 단계의 건설 사업관리(CM)는 사업 초기 단계에 내재된 불확실성을 보완하고, 합리적인 의사결정을 지원한다는 측면에서 그 역할의 중요성이 대두되고 있다. 그 중에서도 사업 기획 단계의 사업 발굴 및 사업 참여방안 검토 업무는 향후 사업의 성공과 실패를 좌우할 수 있는 큰 영향력을 가진 중요한 업무이지만, 의사결정을 위한 각 분야 간의 빈번한 협의, 그리고 이에 따른 계속된 수정, 변경 등과 비효율적인 반복 작업이 문제가 되고 있다. 따라서 이를 효과적으로 수용할 수 있는 업무 프로세스의 변화가 필요하게 되었고, 본 논문에서는 플랜트 프로젝트 기획 단계의 '사업 발굴 및 사업 참여방안 검토'를 대상으로 주요 업무 항목을 도출하고 전문가 자문을 활용한 델파이 분석을 통해 표준화된 업무 프로세스를 정립하였다. 본 논문의 결과는 우리나라 EPC 기업이 해외시장에서 기획 분야의 기술 경쟁력을 확보하고 업무 효율성을 제고할 수 있는 기반을 마련하는 데에 활용될 수 있을 것으로 기대된다.